Early Childhood Development in Sub-Saharan Africa : Issues and Strategies - Colletta, Nat J.; Balachander, Jayshree; Liang, Xiaoyan (World Bank, Washington, DC, 2012)
For many children in Sub-Saharan Africa (SSA), primary school interventions are already too late to prevent irreversible disability or to allow for the development of full adult capacity. Many of the same conditions of poverty that previously placed the under-five at risk of death later leave them at the risk of poor health, malnutrition and impaired mental, social and emotional development. This study, the condition of young children in Sub-Saharan Africa: the convergence of health, nutrition, and early education, describes the condition of young children in Africa and begins to explore strategies to address their condition. It is the first in a series of three studies: the second study is a review of Early Child Development (ECD) programs in SSA and the third will synthesize lessons drawn from the preceding second studies as well as country case studies in Kenya, South Africa, and Mauritius.